Heifers don't care: no evidence of negative impact on animal welfare of growing heifers when using virtual fences compared to physical fences for grazing - D. Hamidi; N.A. Grinnell; M. Komainda; F. Riesch; J. Horn; S. Ammer; I. Traulsen; R. Palme; M. Hamidi; J. Isselstein (Animal, 2022)
Virtual fencing (VF) represents a way to simplify traditional pasture management with its high labour and cost requirements for fencing and to make better use of the ‘beneficial’ agronomic and ecological effects of livestock grazing. In this study, the VF technology (® Nofence, AS, Batnfjordsøra Norway) was used with Fleckvieh heifers to investigate possible welfare impacts on the animals compared to conventionally fenced animals when they were trained to respond correctly to the system. The Nofence® collars (attached to the neck of the heifers) send acoustic signals as a warning when the animals approach the VF line, which was set up by GPS coordinates within the Nofence®-App, followed by an electric pulse when they do not stop or return. The heifers had no experience with VF prior to the study. Two treatments (VF versus physical fencing (PF)) were applied to six groups of four heifers each (three groups per treatment) over three 12-day time replicates. One VF line separated the pasture of the VF group into an accessible or non-accessible area. The control group had a PF line. Both groups were equipped with Nofence® collars (deactivated for the PF group). The trial took place on two adjacent paddocks of 1 000 m2 each following a 12-day schedule which was divided into three sections: visual support of the VF line by a physical barrier (first 2 days), only virtual border without visual support, moving the VF line (on day 8). Each time replicate followed the next successively on different paddocks with two new groups of heifers, which were grazed 5 h daily. During the whole experiment, the behaviour of each of the four animals per group was continuously observed; 2 h a.m., 2 h p.m. Exclusion by the VF line was effective in our trial. None of the heifers crossed the virtual boundary, i.e. the time spent in exclusion zone was zero. The heifers received 2.70 ± 2.63 acoustic signals and 0.30 ± 0.36 electric pulses (mean ± SD) per heifer and hour during all time replicates. Main cattle behaviour on pasture was not affected by the fencing system. Live weight gain, herbage consumption and faecal cortisol metabolites also revealed no significant differences. The duration until the heifers restarted grazing after an electric pulse from the Nofence® collar was significantly shorter than after an electric pulse from the physical fence. We can summarise that in our study, cattle well-being on pasture was not negatively affected by VF compared to PF.